Decentralized Autonomous Organization - Samer Hassan; Primavera De Filippi (Internet Policy Review, 2021)
A DAO is a blockchain-based system that enables people to coordinate and govern themselves mediated by a set of self-executing rules deployed on a public blockchain, and whose governance is decentralised (i.e., independent from central control).
Keywords: 300; Decentralized Autonomous Organization (DAO); Blockchain